Psychopath analysis of the Oliver Quick character from Saltburn (2023) film - Silvani Eka Putri Panjaitan; Setya Ariani (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
The Saltburn (2023) film directed by Emerald Fennell presents an intriguing example of a psychopathic character through its main protagonist, Oliver Quick. At first, Oliver appears as an ordinary scholarship student, but as the story unfolds, his dark personality and manipulative behaviour begin to show. This research aims to analyse the psychopathic characteristics of Oliver Quick using Verstappen’s psychopath theory and Sigmund Freud’s psychoanalysis, including the tripartite model (id, ego, and superego). The research used a qualitative method to analyse the data and draw the conclusion. The data were collected from actions and dialogues in the film. Each psychopathic trait that has been collected was analysed using Freud’s theory by mapping them into id, ego and superego. The results show that Oliver possesses seven key traits of a psychopath: lack of empathy, lack of remorse, superficiality, impulsivity, irresponsibility, compulsive lying, and manipulativeness. These traits are closely connected to Freud’s concept of the id and ego. However, there are no evidence of the superego’s role in Oliver's character, indicating a lack of moral conscience. This research utilized a combination of two psychological frameworks, which are psychopathy and psychoanalysis, to deeply understand a literary character’s behaviour. This research also shows how psychological theory can be applied to literature and film, helping readers and future researchers better recognise and analyse psychopathic behaviour in fictional characters.